KNOWLEDGE IMPROVEMENT OF PRE-CONCEPTION REPRODUCTIVE HEALTH THROUGH ONLINE EDUCATION DURING THE COVID-19 PANDEMIC - Nur Maziyah Hurin'in; Erna Eka Wijayanti; Fedelita Aistania Putri; Prastiwi Novia Puspitasari (Jurnal Penelitian, 2021)
The preconception period starts from the desire to have children until 9 weeks after conception or up to 10 weeks of gestation. This study was to provide health education about pre-conception reproductive health for women of childbearing age during the COVID-19 pandemic. This research was a Quasi-Experimental Design with pretest-posttest group approach. The intervention used was in the form of providing online preconception reproductive health education through video media in the Fatayat NU group, Tuban. The research population was 40 representatives of Fatayat NU throughout Tuban Regency. The sampling technique used total sampling. The research instrument was a questionnaire which was distributed online via the Google Form link on the Whatsapp group, before and after online health education respondents were given a questionnaire. Data analysis used in this research was Wilcoxon. The results showed that most of the respondents at the time of the pretest most of the respondents had sufficient knowledge of 27 respondents (67.5%), then after the post-test, in general, respondents had good knowledge of 31 respondents (77.5%). Data analysis result obtained p-value=0.000, because the p-value0.05 which indicates an increase in Pre-Conception Reproductive Health Knowledge through Online Education During the Covid-19 Pandemic.